Respiratory Disease following Viral Lung Infection Alters the Murine Gut Microbiota - Groves, Helen T.; Cuthbertson, Leah; James, Phillip; Moffatt, Miriam F.; Cox, Michael J.; Tregoning, John S. (Frontiers in Immunology, 2018)
Alterations in the composition of the gut microbiota have profound effects on human health. Consequently there is great interest in identifying, characterising and understanding factors which initiate these changes. Despite their high prevalence, only recently have studies begun to look at how viral lung infections impact on the gut microbiota. There is also considerable interest in whether the gut microbiota could be manipulated during vaccination to improve efficacy. In this highly-controlled study, we aimed to establish the effect of viral lung infection on gut microbiota composition and the gut environment using mouse models of common respiratory pathogens Respiratory Syncytial Virus (RSV) and influenza virus. This was then compared to the effect of live attenuated influenza virus (LAIV) vaccination. Both RSV and influenza virus infection resulted in significantly altered gut microbiota diversity, with an increase in Bacteroidetes and a concomitant decrease in Firmicutes phyla abundance. Although the increase in the Bacteroidetes phyla was consistent across several experiments, differences were observed at the family and operational taxonomic unit (OTU) level. This suggests a change in gut conditions after viral lung infection that favours Bacteroidetes outgrowth but not individual families. No change in gut microbiota composition was observed after LAIV vaccination, suggesting that the driver of gut microbiota change is specific to live viral infection. Viral lung infections also caused an increase in faecal lipocalin-2, suggesting low-grade gut inflammation, and colonic Muc5ac levels. Owing to the important role mucus plays in the gut environment, this may explain the changes in microbiota composition observed. This study demonstrates that the gut microbiota and the gut environment are altered following viral lung infections and that these changes are not observed during vaccination. Whether increased mucin levels and gut inflammation drive, or are a result of, these changes is still to be determined.